Computational Fluid Dynamics Analysis of Breakwater Configurations for Enhanced Coastal Resilience in North Java - Alif Nur Rochmad; Muhamad Rakif panguale; Muhamad Saiful Rahman Hamka; Septaviola Dini Utami (Naval Architecture Department, Kalimantan Institut of Technology, 2026)
The North Java shoreline, much like coastlines elsewhere in the world, continues to suffer the cumulative effects of coastal erosion and storm surge, and breakwaters remain the principal line of defense against this incoming wave energy. A substantial number of these structures, however, are still sized and shaped using generic rules of thumb instead of being calibrated to site-specific wave conditions and seabed characteristics, and the body of published work that tests breakwater configurations against actual North Java conditions is still limited. The present study closes part of that gap by applying a Computational Fluid Dynamics (CFD) simulation framework to examine how breakwater geometry, porosity, and layout govern hydrodynamic behavior under representative wave loading. The free surface and the wave-structure interaction were resolved using the Volume of Fluid (VOF) approach, paired with a turbulence closure model appropriate for free-surface flow. Over the course of the simulated runs, the configurations under investigation brought wave height down from 1.25 m to roughly 0.45 m by t = 20 s. The seaward face experienced its largest dynamic pressure, 38.7 kPa, at t = 10 s, a moment that also coincided with the highest overtopping velocity of 3.42 m/s, even as flow inside the sheltered zone fell to only 0.22 m/s, a rate low enough to let sediment settle out. A subsequent sensitivity analysis showed that raising porosity by 10% together with a gentler slope gradient lowered the peak structural pressure by as much as 15%, yielding design guidance with practical relevance for North Java and comparable coastal settings